PERAN GURU DAN ORANG TUA DALAM MEMBANGUN KARAKTER PEDULI LINGKUNGAN PADA SISWA MELALUI PROGRAM UNGGULAN SEKOLAH ADIWIYATA DI SD NEGERI NGEBUNG BERAN, KULON PROGO - Alifia Nur Latifah; Bahtiyar Heru Susanto (STKIP Subang, 2026)
This study aims to determine the roles of teachers and parents in building students’ environmental care character through the Adiwiyata school flagship program at SD Negeri Ngebung Beran, Kulon Progo, as well as to identify the challenges and solutions encountered in its implementation. The study focuses on three main aspects: the role of teachers, the role of parents, and the environmental care character developed in students through the program. This research employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving third, fourth, and fifth grade teachers, fourth grade students, and parents. The collected data were analyzed through data reduction, data display, and conclusion drawing, based on the predetermined research problems. The results indicate that teachers play significant roles as motivators, facilitators, and organizers in developing students’ environmental care character through habituation, role modeling, structured activities, and the provision of facilities and meaningful learning experiences. Meanwhile, parents act as motivators, role models, and educators who support character development through habituation at home. The Adiwiyata program has proven effective in fostering students’ environmental care character, although several challenges remain, such as students’ inconsistency, varying levels of teacher commitment, environmental facility management issues, and the lack of optimal continuity between school and home environments. Therefore, strengthening collaboration between schools and parents, along with continuous habituation, is necessary to achieve optimal outcomes. Keywords: Teacher Roles, Parent Roles, Environmental Care Character, Adiwiyata School